Evaluation of heavy metal concentrations in rivers Auqui and Paria in the Ancash region, Peru - Barba Regalado, Alejandro Napoleón (2017)
This paper aims to determine the concentrations of heavy metals, specifically, arsenic, cadmium, copper, chromium, manganese, mercury, nickel, lead and zinc; in Auqui and Paria rivers in Ancash, Peru and compare it with the permissible maximum established limits by the World Health Organization (WHO) region.In order to obtain representative samples, a sampling plan in time and space was designed, that is, in each of the four (4) seasons (winter, spring, summer and fall) samples points were taken at five (5) (1000 m and 500 m upstream of the point of collection, the collection point at the entrance and exit of the treatment plant) in three (3) times (beginning, middle and end of the season). The response indicates that the Auqui River manganese concentration is above the maximum allowed limit (0,5 mg/L) and the Paria Riverthere is evidence that lead to think that heavy metal concentrations obtained are below the maximum limits allowed, indicating that water is suitable for human consumption.